A Critical Review of Restorative Justice Policy in the Indonesian Criminal Justice System Post Law No. 1 of 2023 concerning the Criminal Code - Deassy J.A. Hehanussa; Kukun Abdul Syakur Munawar; Muh Fadli Faisal Rasyid; Arianti A Ogotan; Arief Fahmi Lubis (Warmadewa Press, 2024)
This research examines how the amendments introduced by Law No. 1 of 2023 have integrated restorative justice practices into Indonesia's criminal justice system. It explores key obstacles, particularly the tension between restorative justice and the traditional emphasis on punitive measures within society's legal framework. Utilizing a normative descriptive and juridical-analytical approach, the study employs the normative legal method to trace the evolution of Indonesian criminal law and assess the implementation of restorative justice through primary and secondary legal sources. Despite several existing laws supporting restorative justice, the study reveals that the 2023 Criminal Code lacks precise guidelines, resulting in legal ambiguities. Another significant barrier to the broad application of restorative justice is societal resistance, rooted in a cultural preference for punitive justice. The findings suggest that to address these challenges, there is a need to strengthen legislation, provide training for law enforcement, and increase public awareness about restorative justice.